Strategi Komunikasi Pemerintah Indonesia dalam Penanganan COVID-19 pada Majalah TEMPO Edisi Maret-Juli 2020 - Fadjarini Sulistyowati (Jurnal Riset Komunikasi, 2021)
In anticipating COVID-19 pandemic, policies directed by the government needs to be communicated to the people with clarity and transparency. Unplanned communications will lead to consequences in the public sector. Public communication that is not planned carefully will cause panic and distrust in society.. In the beginning of Covid-19 pandemic, the government must construct precise coomunication strategies in order to convey structured policies and information to society. Communication strategies includes the contents of the messages that are going to be conveyed in order to provide clarities regarding government’s policies to address Covid-19 pandemic. The media works as a tool to convey messages from the government to the society by constructing government’s communication strategies in addressing covid-19 using the news. Media can create perceptions withing society in regards to the news. This research is being done to understand the frame of Tempo Magazine in government’s communication strategies to handle COVID-19 pandemic. Analysis technique using analysis by Entmann. News collection is being done from early March to late July 2020. News related to the government’s communication strategies to handle COVID-19 pandemic are being selected. Results show that government is not ready yet to implement accurate communication strategies in handling COVID-19, from the early COVID-19 pandemic, PSBB (Pembatasan Sosial Berskala Besar) to the new normal era. Tempo magazine can provide control towards policies that are relevant to government’s communication strategies in dealing with Covid-19